Peran Microteaching sebagai Langkah Awal dalam Pengembangan Profesionalisme Calon Guru dalam Program PPL - M, Matmudi; El-Yunusi, Muhammad Yusron Maulana (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Microteaching activities can prepare students who will become teachers to master pedagogical skills. The aim of this research is to see how students who will become teachers at Sunan Giri University Surabaya apply microteaching. It is hoped that the results of the analysis can help lecturers who are preparing students to become teachers and student teachers to anticipate standards that need to be improved. The role of microteaching in improving the teaching skills of prospective teachers is the subject of this research. Qualitative methods with literature studies were used. Data is collected by conducting relevant searches on academic platforms such as Google Scholar. The results of the analysis show that microteaching is an effective method for preparing students to teach systematically. This practice not only helps prospective educators master basic teaching skills, but also provides experience.